Desain dan Implementasi Sistem Instrumentasi Aliran Fluida Berbasis Supervisory Control And Data Acquisition (SCADA) dan dan Programmable Logic Controller (PLC) - Hasna Humaira, Raden Roro; Zaki Hamidi, Eki Ahmad; Ridwan, Azwar Mudzakkir (ISTEK, 2025)
One of the main challenges in the development of instrumentation systems for industrial fluid flow processes is the requirement for real-time pressure monitoring and control to prevent abnormal conditions that may lead to operational failures. This study aims to design and develop an instrumentation system capable of performing monitoring, control, and early warning functions through the integration of a pressure transmitter, Haiwell AC12M0R PLC, HMI, and SCADA using TCP/IP and Wi-Fi communication protocols. The system design includes hardware development, ladder diagram programming, and configuration of a cloud-connected HMI–SCADA interface. System testing was conducted by varying pressure setpoints to simulate different operating conditions. The test results indicate that the system operates as designed, as evidenced by alarm activation at a pressure of 6 bar, proportional opening of the Pressure Control Valve (PCV) when the pressure exceeds the 5 bar setpoint, and activation of safety functions under high-high pressure conditions at 9 bar, where the system triggers an alarm, closes the Shut Down Valve (SDV), and automatically stops the pump. The PCV response time was recorded at 0.1–0.2 seconds, while the SDV fully closed within 5–6 seconds. All process data can be monitored in real time through the HMI and cloud-integrated SCADA system, enabling remote monitoring via smartphone. Overall, the developed instrumentation system prototype functions in accordance with the control logic and performs reliably under the simulated operational scenarios.